Kontribusi Ustazah Tuty Sukayat dalam Pembinaan Keagamaan di Yayasan An-Nuriyah - Noor Bekti Negoro; Alia Nawal Salsabila; Damar Refina Hanin (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Community-based dakwah plays a strategic role in shaping the religious culture of urban societies, yet the contributions of female preachers at the local level remain largely undocumented in academic literature. This study examines the dakwah journey of Ustazah Tuty Sukayat analyzes the impact of An-Nuriyah Foundation's religious programs on the spiritual life of the Meruya Selatan community, Kembangan, West Jakarta. A qualitative biographical design was employed, with data collected through in-depth interviews, participatory observation, documentation. Findings reveal that since 1979, Ustazah Tuty has consistently conducted Islamic study sessions, diniyah madrasah, daily worship guidance, Ramadhan programs, preacher training courses, utilized various media including books, radio, YouTube. A participatory, educative, contextual approach has proven effective in enhancing religious literacy fostering a sustainable religious culture within the community. The study underscores the urgency of cadre regeneration digital media optimization to ensure the continuity of community-based dakwah.